Does Supply Chain Information Sharing Affect the Business Performance of Batik MSMEs in Yogyakarta City? - Novanty, Tety; Liestyana, Yuli; Utami, Yekti; Wahyuningsih, Tri; Satmoko, Agung (AIBPM Publisher, 2023)
This study examines the impact of supply chain information sharing on business performance as mediated by operational performance and supply chain integration. This study uses a questionnaire to collect data. This study includes primary data collected from 53 respondents and is focused on batik MSMEs in Yogyakarta City, Special Region of Yogyakarta, Indonesia. PLS-SEM analysis using SmartPLS 4.0 is the research's analysis method. The results of this study are: 1. Supply chain information sharing positively affects supply chain integration. 2. Supply chain information sharing positively affects business. 3. Supply chain information sharing positively affects operational performance. 4. Supply chain integration positively affects operational performance. 5. Supply chain integration positively affects business performance. 6. Operational performance positively affects business performance. 7. Supply chain information sharing positively affects business performance mediated by supply chain integration. 8. Supply chain information sharing positively affects business performance mediated by operational performance. The research team suggests that batik MSMEs in Yogyakarta City should work to adapt products to satisfy urgent customers' needs quickly.